Genome editing abrogates angiogenesis in vivo - Xionggao Huang (Nature Portfolio, 2017)
Abnormal angiogenesis causes many ocular diseases. Here the authors employ CRISPR/Cas9 gene editing technology to silence VEGFR2, a major regulator of angiogenesis, in retinal endothelium and abrogate angiogenesis in the mouse models of oxygen-induced retinopathy and laser-induced choroid neovascularization.